Investigation of protocol design for molecular communication nanonetworks - Liu, Dong (2014)
Nanotechnology is a new emerging research area with great potential. With the development of nano-manufacture, it’s possible to fabricate nanomachines in bio-hybrid ways. However, single nanomachine has limited capabilities in terms of power consumption and computation ability. Hence, it is a must to discover a new paradigm of communication networks, nanonetworks.